2013
DOI: 10.1016/j.ejps.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of drug transporter expression by all-trans retinoic acid in hepatoma HepaRG cells and human hepatocytes

Abstract: All-trans retinoic acid (atRA) is the active form of vitamin A, known to activate retinoid receptors, especially the heterodimer retinoid X receptor (RXR):retinoic acid receptor (RAR) that otherwise may play a role in regulation of some drug transporters. The present study was designed to characterize the nature of human hepatic transporters that may be targeted by atRA and the heterodimer RXR:RAR. Exposure of human hepatoma HepaRG cells and primary human hepatocytes to 5 M atRA down-regulated mRNA levels of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…We did not use tumor cell lines to examine endogenous OCT expression and functionality because there is a strong downregulation in all cancer cell lines, which makes these models highly artificial and defective [ 21 ]. Furthermore, cancer cell lines have been extensively studied, showing very different results compared to primary hepatocytes [ 30 ]. In primary WT and Oct3 −/− hepatocytes Slc22A1 mRNA expression was significantly upregulated after 24 hours of quinine treatment in vivo (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…We did not use tumor cell lines to examine endogenous OCT expression and functionality because there is a strong downregulation in all cancer cell lines, which makes these models highly artificial and defective [ 21 ]. Furthermore, cancer cell lines have been extensively studied, showing very different results compared to primary hepatocytes [ 30 ]. In primary WT and Oct3 −/− hepatocytes Slc22A1 mRNA expression was significantly upregulated after 24 hours of quinine treatment in vivo (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Increased OATP1A2 expression could contribute to breast cancer pathogenesis because increased influx of the substrate oestrone 3‐sulfate could drive tumour cell proliferation (Meyer zu Schwabedissen et al, ). In contrast, the CAR ligand phenobarbital down‐regulated OATP1B3 and OAT2 in human liver slices (Jigorel et al, ), and the retinoic acid receptor ligand all‐ trans ‐retinoic acid down‐regulated OATP1B1 and OATP2B1 mRNAs and immunoreactive proteins in primary human hepatocytes (Le Vee et al, ). Exposure of human liver‐derived cells to AhR ligands repressed OATP1B1, OATP1B3 and OAT2 mRNAs (Jigorel et al, ; Le Vee et al, ).…”
Section: Transcriptional Regulation Of Slc and Slco Genesmentioning
confidence: 99%
“…Our data showed that TP treatment induced hepatic damage both in vitro and in vivo , indicating successful modeling and relieving effect of ISL combined treatment, which is consistent with our previous studies ( Cao et al, 2016a , b ). The present study for the first time used human normal L02 hepatocytes rather than hepatoma cells or rodent hepatocytes, which is as close to clinical practice as possible, since there are differences in physiological conditions as well as distributions and expression levels of transporters between human normal hepatocytes and hepatoma cells or rodent hepatocytes ( Nicolaou et al, 2012 ; Le Vee et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%